Immune Checkpoint Inhibitor-Associated Nephrotoxicity - Mamlouk, Omar; Danesh, Farhad R (Nephron (2015), 2024)
The clinical indications for immune checkpoint inhibitors (ICIs) are rapidly expanding. However, adverse events affecting multiple organs, including kidneys leading to ICI-associated acute kidney injury (AKI), remain a significant challenge with ICI therapy. Although AKI is considered a rare complication, it can be severe and result in treatment interruption or discontinuation of ICIs. Despite a generally favorable kidney prognosis, the possibility of re-challenging ICI therapy remains a subject of debate, particularly for patients who have exhausted other treatment options or experienced severe AKI. Subject of Review: In a recent review article, Sprangers et al. provide a comprehensive overview of the possible mechanisms and clinical manifestations of ICI-associated AKI [Nat Rev Nephrol. 2022;18(12):794-805]. The authors propose a practical strategy for diagnosing and managing suspected cases of ICI-associated AKI, which includes identifying a subset of eligible patients who may be re-exposed to ICIs following an episode of AKI. Second Opinion: The authors of the review article offer several recommendations on the diagnosis and treatment of ICI-associated nephrotoxicity. While we generally agree with the recommendations proposed by the authors, it is important to acknowledge that the available data primarily rely on small retrospective studies, as the authors have recognized. In addition, there are two key questions that need be carefully addressed in future studies: (1) the optimal dose and duration of corticosteroids and the use of alternative immunosuppressive agents in patients with ICI-associated nephrotoxicity and (2) a clear guideline for restarting ICI treatment in patients with AKI who have not fully recovered their kidney function.